Characterization of Cancer Stem Cells in Colon Adenocarcinoma Metastasis to the Liver - Humphries, Hugo N.; Wickremesekera, Susrutha K.; Marsh, Reginald W.; Brasch, Helen D.; Mehrotra, Shreeja; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2018)
Background 50% of colorectal cancer (CRC) patients develop liver metastasis. This study identified and characterized CSCs within CRC metastasis to the liver (CRCML). Methods DAB immunohistochemical (IHC) staining was performed on nine CRCML samples for embryonic stem cell (ESC) markers OCT4, SOX2, NANOG, c-Myc and KLF4. Immunofluorescent (IF) IHC staining was performed to investigate co-expression of two markers. NanoString analysis and colorimetric in situ hybridization (CISH) were performed on four snap-frozen CRCML tissues for transcript expression of these ESC markers. Cells stained positively and negatively for each marker by IHC and CISH staining were counted and analyzed. Results DAB IHC staining, NanoString and CISH analyses demonstrated the expression of OCT4, SOX2, NANOG, c-Myc and KLF4 within CRCML, except for SOX2 which was below detectable levels on NanoString analysis. IF IHC staining showed the presence of a SOX2+/NANOG+/KLF4+/c-Myc+/OCT- CSC subpopulation within the tumor nests, and a SOX2+/NANOG+/KLF4+/c-Myc+/OCT4- CSC subpopulation and a SOX2+/NANOG+/KLF4+/ c-Myc+/OCT4+ CSC subpopulation, within the peritumoral stroma. Conclusion The novel finding of three CSC subpopulations within CRCML provides insights into the biology of CRC.